1994
DOI: 10.1017/s0950268800068424
|View full text |Cite
|
Sign up to set email alerts
|

Application of physico-chemical typing methods for the epidemiological analysis ofSalmonella enteritidisstrains of phage type 25/17

Abstract: SUMMARYEighty-nine Salmonella enteritidis phage type 25/17 strains isolated from a localized outbreak in the German state Nordrhein-Westfalen (outbreak NWI) could not be further differentiated by biochemotyping and plasmid pattern analysis. They were submitted to a complex typing system consisting of modern physico-chemical analytical procedures. In lipopolysaccharide pattern analysis the strains proved to be homogeneous. In multilocus enzyme electrophoresis, outer membrane and whole cell protein pattern (WCPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…FT-IR spectroscopy has been used in combination with other techniques for qualitative studies on intraspecific diversity (Seltmann et al, 1994(Seltmann et al, , 1995Irmscher et al, 1999 ;Stan-Lotter et al, 1999), but, as far as we are aware, the method has not previously been applied to quantitative assessment of intraspecific diversity, i.e. to quantification of the degree of heterogeneity.…”
Section: Abbreviation : Ft-ir Fourier-transform Infraredmentioning
confidence: 99%
“…FT-IR spectroscopy has been used in combination with other techniques for qualitative studies on intraspecific diversity (Seltmann et al, 1994(Seltmann et al, , 1995Irmscher et al, 1999 ;Stan-Lotter et al, 1999), but, as far as we are aware, the method has not previously been applied to quantitative assessment of intraspecific diversity, i.e. to quantification of the degree of heterogeneity.…”
Section: Abbreviation : Ft-ir Fourier-transform Infraredmentioning
confidence: 99%
“…These studies have shown that it is possible to discriminate among various microorganisms at the genus, species, and strain level (14, 21-22, 25, 27, 29-32, 34, 49), and studies report the ability to differentiate microorganisms from various serogroups (21)(22)(23)37). Furthermore, the use of FT-IR spectroscopy to identify drug resistance has also been investigated (3,42).…”
mentioning
confidence: 99%
“…The patterns of the O-antigenic lipopolysaccharides (LPS) and the OMPs as well as the whole-cell protein profiles (WCPPs) were determined by SDS-PAGE as described earlier (22). MLEE was performed in a starch gel under nondenaturing conditions as described previously.…”
Section: Methodsmentioning
confidence: 99%